Training in digital skills for students with visual disabilities - Jose Roberto Barboza Junior; Mario Chacón-Rivas (Dialogia)
In today's society, information in digital formats provides support in the fields of health, education, many others. Therefore, it is essential to have the knowledge and skills to access it. Therefore, the processes of training digital skills are a basic and highly valuable element for people in today's society. However, for people with disabilities, these digital skills present a series of barriers that hinder their interaction and personal and independent development. For this reason, it is urgent that the institutions and organizations responsible for the education and training processes be aware of and committed to the training of digital skills using all accessibility and inclusion criteria. This work presents the experiences that were achieved in Costa Rica by developing a training workshop on digital skills for 12 visually. A set of conclusions is presented that are expected to be helpful for organizations that train skills in people with disabilitie.